THE EFFECT OF EXPERIENTIAL MARKETING ON REPURCHASE INTENTION WITH CUSTOMER SATISFACTION MEDIATION AND REPUTABLE BRAND AT SELF COOKING RESTAURANT - Rizky Ramdhan Aprian Aditama; Tulus Haryono (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The purpose of this study was to examine and analyze the effect of experiential marketing on repurchase intentions mediated by customer satisfaction and moderated by reputable brands. The data collection method uses a survey, the data collected is 225 customers who have purchased at a self-cooking restaurant in the city of Surakarta. Data analysis using PLS-SEM analysis. Based on the data and research results, it is known that experiential marketing which includes sense, feel, think, act and relate has a positive and significant effect on repurchase intentions. The results showed that the mediating variable of customer satisfaction had a positive and significant effect on mediating the relationship between experiential marketing and repurchase intention. In this study, the moderating variable of reputable brands did not strengthen experiential marketing on repurchase intentions. Keywords: Self-cooking restaurant, experimental marketing, repurchase intention, customer satisfaction, reputable brand